Logic Colloquium '01 proceedings of the Annual European Summer Meeting of the Association for Symbolic Logic, held in Vienna, Austria, August 6-11, 2001 - Baaz, Matthias 1960-; Friedman, Sy-David 1953-; Krajíček, Jan 1960- (Cambridge University Press, 2016)
Since their inception, the Perspectives in Logic and Lecture Notes in Logic series have published seminal works by leading logicians. Many of the original books in the series have been unavailable for years, but they are now in print once again. This volume, the twentieth publication in the Lecture Notes in Logic series, contains the proceedings of the 2001 European Summer Meeting of the Association for Symbolic Logic, held at the Vienna University of Technology. Two long articles present accessible expositions on resolution theorem proving and the determinacy of long games. The remaining articles cover separate research topics in many areas of mathematical logic, including applications in computer science, proof theory, set theory, model theory, computability theory, linguistics and aspects of philosophy. This collection will interest not only mathematical logicians but also philosophical logicians, historians of logic, computer scientists, formal linguists and mathematicians working in algebra, abstract analysis and topology
Title from publisher's bibliographic system (viewed on 14 Apr 2017)
Keywords: Logic, Symbolic and mathematical / Congresses; Konferenzschrift